POTENSI WILAYAH UNTUK PENGEMBANGAN USAHASAPI POTONGTRADISIONAL DIKECAMATAN IV NAGARIKABUPATEN SIJUNJUNG - Gusniati, Reni; Rianto, Slamet; Yuherman, Yuherman (Pendidikan Geografi, 2013)
This research is Â District Of IV Nagari Sub-Province of Sijunjung, with aim to to know regional potency for the development of crosscut ox effort either from facet : ( I) Potency human resource ( SDM), ( 2) Potency natural resources ( SDA), and ( 3) Condition of institute of supporter, which there are [in] District Of IV Nagari Sub-Province of Sijunjung.This research use descriptive method that is Â research to occurence which or have occurence. .Population in this research is entire/all family head breeder of crosscut ox exist in District Of IV Nagari Sub-Province of Sijunjung.Technique intake of data pass observation / direct perception of leisure and spreading of enquette, becoming sampel in occurence.Technique analyse data performed within this research with percentage analysis to potency development of crosscut ox region.Result of research find : ( 1) Evaluated from human resource aspect which is IV Nagari,Kecamatan, owning potency able to support development of ox effort .(2) While seen from natural resources aspect which consist of : availibility of water, farm potency and availability of green which is very support. ( 3) available Institute also support development of crosscut ox effort in District of IV Nagari among others is institute of Finance exploiting of institute, institute support and role of institute.